As consequências causadas pelo consumo de água do rio Tabatinga na comunidade nossa senhora do Perpetuo Socorro no município de Abaetetuba-PA - CARDOSO, Adriana Farias (2019)
It is known that any change in the aquatic environment can cause damage to any ecosystem and one of the major challenges that current and future generations may face would be various pathologies affected by the consumption of contaminated waters. Thus, this article aimed to conduct a survey from an exploratory field research in the community of Our Lady of Perpetual Help. The research emerged based on the problem identified with the observation and experience in locus (Located on Sirituba Island in Rural Zone in the Municipality of Abaetetuba/PA), being developed through literature reviews and field research with observations and semi-structured interviews for residents. from the community. The data collected through the interviews showed that the community suffers from problems associated with water consumption, with itching, diarrhea, stomach pain, body blemishes and hair loss. These symptoms, according to the interviewees, may possibly be related to the social and environmental impact of various types of waste discharged from the source of water for daily consumption, in addition to the proximity to the industrial center.